Application of a SODOSM-based MCDM method for evaluating comprehensive fruit quality: A case study of pineapple - Ru Zhou; Ling Lin; Qi Li; Shaodong Zeng; Jianzhi Ye; Cheng Luo (PLoS ONE, 2025)
This study constructs an evaluation index system and model by integrating objective evaluation methods such as the entropy weight method and TOPSIS with subjective evaluation methods like Delphi and AHP. By analyzed the scatter plots of the comprehensive quality evaluation values of commodity quality before and after weighting, it was found that the quality evaluation values before and after weighting are highly correlated, with correlation coefficients of 0.908 respectively. The weighting method employed in this study only weights the quality evaluation values within a certain range to reflect the subjective preference of consumers, without destructively altering the quality evaluation. This study aims to construct an evaluation index system and model that not only satisfies subjective preferences but also objectively reflects the true quality of pineapples from multiple indicators and dimensions.